Asuhan Keperawatan Pada Ny. Y dengan Post Sectio Caesaria Indikasi Ketuban Pecah Dini di Bangsal Mawar III RSUD Surakarta - Arifin, Annisa Zulfa, Faizah Betty R., A., S.Kep ., M.Kes (2015)
Background: Various problems that endanger pregnant women today are very prone to occur, this is due to many incidents or cases which are found in the world of obstetrics related to pregnancy danger signs such as the genesis of early Amniotic Rupture (KPD) for example. One of the things you can do to cope with the KPD was by means of a caesarean section. Aim of Research: to study about nursing care on mothers with post sectio caesaria amniotic rupture early indications include assessment, nursing diagnosis, nursing interventions, implementation, and evaluation. Results: after nursing care during 3x24 hours obtained results soreness felt diminished, can perform daily activities, knowing and being able to take care of wounds post sectio caesaria. Conclusion: team work between client or family and care giver was absolutly need for success on nursing care of the patients so that the problem of nursing on patients about pain, barriers, and lack of knowledge mobilization can be implemented properly and most problems can be resolved in part through completely.